FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN SUSU FORMULA PADA BAYI 0-6 BULAN DI WILAYAH KERJA PUSKESMAS LINGKAR TIMUR KOTA BENGKULU - Desi Fitriani (STIKes CHMK, 2023)
The large number of mothers who give formula milk at an early age is due to many factors such as lack of knowledge and attitudes of mothers about the importance of exclusive breastfeeding. This study aims to study the factors associated with formula feeding in infants 0-6 months in the Working Area of ​​the East Ring Health Center in Bengkulu City. The research design used cross sectional. The population in this study were mothers who had babies aged 6-12 months in the Working Area of ​​the East Circle Health Center in Bengkulu City, totaling 37 people who were taken using the Accidental Sampling technique. Data collection uses primary data and secondary data. Data analysis used univariate, bivariate and multivariate analysis. The results of the study were: Of the 37 mothers, 22 (59.5%) gave formula milk; Of the 37 mothers, there were 18 (48.6%) mothers who had less knowledge; Of the 37 mothers, there were 19 (51.4%) mothers who were favorable about formula milk; Of the 37 mothers, 23 (62.2%) had supportive families. There is a significant relationship between knowledge and formula feeding in infants 0-6 months in the Working Area of ​​the East Ring Health Center in Bengkulu City with the moderate category. There is a relationship between mother's attitude and giving formula milk to babies 0-6 months in the Working Area of ​​the East Ring Health Center in Bengkulu City with the close category. There is a categorical relationship between family support and giving formula milk to babies 0-6 months in the Working Area of ​​the East Circle Health Center in Bengkulu City with a close category. It is hoped that health workers will be able to provide counseling and health promotion to mothers and families about what formula milk is and when is the right time to give formula milk, as well as side effects if it is given too soon before 6 months. Keywords: Knowledge, Attitude, Husband's Support, Formula Milk